Study on the Influential Factors of Noise Characteristics in Dense-Graded Asphalt Mixtures and Field Asphalt Pavements - Zhaoyang Guo; Junyan Yi; Sainan Xie; Jianpeng Chu; Decheng Feng (Shock and Vibration, 2018)
Determining the influential factors of noise characteristics in dense-graded asphalt mixtures and field asphalt pavement is important in constructing highways that are both low noise and environmentally friendly. In this study, the effects of nominal maximum aggregate size, asphalt binder type, air void percentage, and the service life of pavement on the noise absorption characteristics of asphalt mixtures were first investigated in laboratory. Thereafter, tire/pavement noise measurements were conducted on different types of dense-graded asphalt pavements. The effects of the service lives of the pavements, the types of the pavements, driving speeds, and test temperatures on the noise levels of the pavements were also studied. The Zwicker method is used to calculate psychoacoustic parameters on the tire/pavement noise spectrum. The laboratory results indicate that reducing the nominal maximum aggregate size, using rubber asphalt, and increasing air void percentage as well as surface texture depth improve the sound absorption performance of asphalt mixtures. The field measurements show that laying down asphalt pavements with a shorter service life or larger texture depth, using rubber asphalt, reducing traffic speed, and increasing air temperature can reduce noise.